ANALYSIS OF BLACK RICE FARMING COMPETITIVENESS (A CASE STUDY IN MERKARWANGI VILLAGE, CISAYONG DISTRICT, TASIKMALAYA REGENCY, WEST JAVA PROVINCE) - kuswarini kusno; Galih Wilarko; Muhammad Arief Budiman; Lies Sulystiowati (AGROLAND The Agricultural Sciences Journal (e-Journal), 2020)
Black rice is a functional food so that it is not only to meet food needs, but also to maintain the health of consumers. For farmers, producing black rice will be more profitable because the selling value is higher than other types of rice. However, not many consumers and farmers are aware of this, resulting in unstable black rice production. In this free trade era, the opportunity to export a commodity or penetrate the international market is getting bigger. Therefore, it is necessary to study the competitiveness of black rice to determine its potential.The purpose of this research was to identify competitiveness through competitive advantage and comparative advantage as well as the impact of government policies. The research design used was quantitative with survey techniques. Data were analyzed using the Policy Analysis Matrix (PAM). The results showed that black rice was competitive both competitively and comparatively, indicated by the value of PCR < 1 = 0.568 and DCR < 1 = 0.521. Therefore, 1) black rice farming was efficient financially and economically, and 2) black rice has the potential to be exported. The impact of government policies on black rice farming has overall reduced farmers' income. In addition, government policies also inhibited black rice exports as indicated by the value of NPCO < 1 = 0.793 and prevented farmers from exporting inputs as indicated by the value of NPCI < 1 = 0.565.